Comparisonal Analysis Of Gross Profit And Net Profit At PT. Charoen Pokphand Indonesia, Tbk And PT. Japfa Comfeed Indonesia, Tbk - Nurfaujiah Nurfaujiah; Aliah Pratiwi (Jurnal Ilmu Manajemen Profitability, 2023)
This study aims to analyze the presence or absence of differences in Gross Profit  and Net Profit between PT. Charoen pokphand Indonesia, Tbk and PT. Japfa Comfeed Indonesia, Tbk. This type of research used in this study is a comparative study (comparison). Comparative research is used to determine the comparison of  Gross Profit  dan Net Profit between PT. Charoen pokphand Indonesia, Tbk (X1) and PT. Japfa Comfeed Indonesia, Tbk (X2). The variables in this study are Gross Profit dan Net Profit. The sampling method used is the purposive sampling method, which is to take the sample determined earlier based on the aims and objectives of the study and the sample in this study is the financial statements on PT. Charoen pokphand Indonesia, Tbk and PT. Japfa Comfeed Indonesia, Tbk for 6 years starting from 2016  to 2021. Analysis The data used is t-test Two Independent samples. The analysis shows that there is no difference in Gross Profit between PT. Charoen pokphand Indonesia, Tbk and PT. Japfa Comfeed Indonesia, Tbk, the results of data interpretation can be compared  and . If  ≤ , then H0 is accepted and Ha is rejected. So {(1,323) ≤ (2,228)}, then H0 is accepted and Ha is rejected. The analysis shows that there is a  difference in Net Profit between PT. Charoen pokphand Indonesia, Tbk and PT. Japfa Comfeed Indonesia, Tbk, the results of data interpretation can be compared  and . If  , then Ha is accepted and H0 is rejected. So {(2,967) (2,228)}, then Ha  is accepted and H0 is rejected.